2009
DOI: 10.4315/0362-028x-72.12.2611
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Activity of Glutaraldehyde-like Compounds from Olive Products

Abstract: The bactericidal effects of several olive compounds (nonenal, oleuropein, tyrosol, the dialdehydic form of decarboxymethyl elenolic acid either free [EDA] or linked to tyrosol [TyEDA] or to hydroxytyrosol [HyEDA]), other food phenolic compounds (catechin, epicatechin, eugenol, thymol, carvacrol, and carnosic acid), and commercial disinfectants (glutaraldehyde [GTA] and ortho-phthalaldehyde [OPA]), were tested against strains of Pseudomonas fluorescens, Staphylococcus aureus, Enterococcus faecalis, and Escheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 18 publications
5
46
0
1
Order By: Relevance
“…In contrast, these compounds are not detected in any of the brines from olives treated with NaOH, as has already been reported (Medina et al, 2008). EDA and HyEDA, together with oleoside-11-methyl ester, are the substances in olive brines that showed the greatest antimicrobial activity (Brenes et al, 2011;Medina et al, 2009), as it was also confirmed in the present study. The curve fitting approach used in this work give us more detailed information on the pathogen responses in the olive brines (maximum death rate, residual populations, time for 4 log 10 reduction, etc.)…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, these compounds are not detected in any of the brines from olives treated with NaOH, as has already been reported (Medina et al, 2008). EDA and HyEDA, together with oleoside-11-methyl ester, are the substances in olive brines that showed the greatest antimicrobial activity (Brenes et al, 2011;Medina et al, 2009), as it was also confirmed in the present study. The curve fitting approach used in this work give us more detailed information on the pathogen responses in the olive brines (maximum death rate, residual populations, time for 4 log 10 reduction, etc.)…”
Section: Discussionsupporting
confidence: 90%
“…A lower concentration of antimicrobial compounds requires more time of contact to reduce the initial population. Medina et al (2009) observed that low concentrations of HyEDA (0.075 mM) are able to reach a 4 log 10 reduction of S. aureus in 15 minutes. Data from this work are in line with those previous observed.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We determined MIC values of 1200-2400 μg/ml for P. aeruginosa, E. faecalis, and E. durans strains (see Table 1). Similar results for P. aeruginosa were reported by Medina et al (2009) and Joshi et al (2013). A significantly lower MIC value of 273 μg/ml was reported by Bassole et al (2010).…”
Section: Discussionsupporting
confidence: 87%
“…shedding rate only after a prolonged period of administration (28 days). Previous studies have focused on the effects of olive by-product polyphenols on foodborne pathogens in in vitro trials [20,21], typically involving Gram-negative bacteria. No data are available on Campylobacter spp.…”
Section: Resultsmentioning
confidence: 99%